Determination of 2,3,5-Triphenyltetrazolium Chloride Based on Flavinic Acid and 5-Nitrobarbituric acid Ion Pair Membrane - Fathi Elsaid, A.G.; Rizk, N.M.H.; Hamdy Matter, A.B. (Asian Journal of Chemistry, 2010)
A novel ion-selective membrane sensors consisting of flavinic acid/2,3,5-triphenyltetrazolium chloride (TTC) ion pair and 5-nitrobarbituric acid/TTC ion pair dispersed in a PVC matrix plasticized with dioctyl sebacat (DOS) is described. The electrodes shows a stable, near-Nernstian response for 1 × 10-2–5 × 10-6 M TTC at 25 °C with cationic slope of 56 ± 0.5 over the pH range 8-10. The lower detection limit and the response time are 5 × 10-6 M and 30-60 s, respectively. Selectivity coefficients for TTC relative to a number of interfering substances were investigated. There is negligible interference from many cations and anions. The determination of 0.5- 200 mg mL-1 of TTC in aqueous solutions shows an average recovery of 99.0 % and a mean relative standard deviation of 1.4 % at 50.0 mg mL-1. The direct determination of TTC in spiked wastewater and soil gave results that compare favorably with those obtained by the atomic absorption spectrophotometric method. The electrodes were successfully applied for the determination of TTC in wastewater and soil using potentiometric titration.